フジ コウロ 1972-1973 ニオケル ヒョウメン カイスイ チュウ ノ クロロフィル αリョウ ノ ブンプ - 黒田, 一紀; クロダ, カズノリ; KURODA, Kazunori (国立極地研究所, 1978)
P(論文) 1972年11月25日から1973年4月16日まで,第14次南極地域観測隊海洋生物定常観測の一環として,「ふじ」航路に沿って表面海水中のクロロフィル色素を螢光法によって測定した.クロロフィル-α量は白木沿岸,マカッサル海峡,亜南極域,南極収束線以南の東経82°～104°付近,東経15度線の63°～67°S付近,アフリカ南岸付近,マラッカ海峡で高かった.各水域のクロロフィル-α量およびクロロフィル-αとフェオフィチンの和に対するクロロフィル-αの百分率の平均値を比較すると,南極域と亜南極域でクロロフィル-α量は最も高く,同時にクロロフィル-αの百分率も高かった.マラッカ海峡,セレベス海,マカッサル海峡ではクロロフィル-α量は高く,沿岸水の特徴を示していた.インド洋,北西太平洋,南シナ海のクロロフィル-α量は低く,また,クロロフィル-αの百分率も低かった. Measurements of chlorophyll-α and phaeophytin at the surface were carried out by fluorometric methods on board the FUJI from November 1972 to April 1973. The chlorophyll-α contents were relatively high in the coastal region of Japan, the Makassar Strait, the Subantarctic region, the area from 82° to 104°E south of the Antarctic Convergence, the area from 63° to 67°S on the meridian of 15°E, the area off the southern coast of Africa and the Malacca Strait. The distributional patterns of chlorophyll-α obtained by the present investigation were generally similar to those of the previous investigations. The mean values of chlorophyll-α and percentages of chlorophyll-α to the sum of chlorophyll-α and phaeophytin were extremely low in the Indian Ocean, the western North Pacific Ocean, and the South China Sea. On the other hand, in the Subantarctic and the Antarctic regions, they were high, and in the Malacca Strait, the Celebes Sea and the Makassar Strait the concentrations of chlorophyll-α were almost equal to those in the Subantarctic and the Antarctic regions. departmental bulletin paper